UPAYA MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA PADA MATERI GOTONG ROYONG MENGGUNAKAN MODEL PBL SISWA KELAS IV UPT SD NEGERI DOROMUKTI TUBAN - Jihan, Alfin; Wendri Wiratsiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve student learning outcomes in Pancasila education subjects, especially in the material of mutual cooperation, by using the problem based learning (PBL) model. The research method used is classroom action research (PTK) with a quantitative and qualitative approach. The subjects of this study were students in one of the elementary/middle schools UPT SD Negeri Doromukti Tuban who had difficulty in understanding the concept of mutual cooperation in depth. In this learning process, two cycles were carried out, namely cycle 1 and cycle 2. Each cycle includes 4 stages, namely planning, implementation, observation, and reflection. The subjects of this study were teachers and 11 students of class IV UPT SD Negeri Doromukti Tuban. Data collection techniques used written tests. The results of the increase showed an increase from cycle 1 to cycle 2. In cycle 1, the results of the study were obtained from 5 students 45.5% were said to be incomplete while 6 students 54.5% were said to be complete were the average learning outcomes of class IV students. The results of this study indicate an increase in learning outcomes in students and efforts to improve the quality and quality of Indonesian education. connecting lesson materials with daily social interactions can improve understanding of the material more optimally in students.